LGBT PERSPEKTIF HADIS NABI SAW. - M. Asna Mafaza, Izza Royyani (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2020)
One issue that is still very hotly discussed in the public roar today is the issue of Lesbian, Gay, Bisexual and Transgender. LGBT is related to sexual behavior. It refers to a situation in which the perpetrator has a sexual disorder. This is usually caused by their association, social constructs and their unawareness of their sexual identity. Their existence until now is of course very difficult to accept among the general public, because they are considered a deviation and contrary to the moral and religious values that exist in society and many have blasphemed the perpetrators as perpetrators of major sins that need to be punished. In Islam, the LGBT phenomenon has existed since the time of Prophet Luth, where his people have committed very perceptive acts, namely channeling sexual lust to the same sex, their behavior is called sodom. And Islam strictly forbids this, as evidenced by the descent of the disaster to the people of the Prophet Lut. that time. This Islamic view of LGBT can be found explicitly in the explanation of the hadith of Raslullah saw. So to understand this phenomenon, a study of the hadith in question is conducted. The study of this hadith is carried out to become the basis for addressing the LGBT phenomenon that is rife in Indonesia. However, to apply the understanding of the hadith as a whole is certainly not easy to do, because Indonesia is not a country that makes Islam a system in the state. It has its own point of view regarding the LGBT phenomenon. Therefore, it is very important to conduct an in-depth study of the hadiths that talk about LGBT so that this phenomenon can be properly addressed and resolved, especially in the context of Indonesia which highly respects human rights